The EVA (Early Vascular Aging) Study: Association of Central Obesity With Worse Arterial Health After Preeclampsia - Paquin, Amélie; Werlang, Ana; Coutinho, Thais (Journal of the American Heart Association, 2023)
Background Women with preeclampsia have a higher risk of cardiovascular disease. This is partly explained by the worse arterial health after preeclampsia. Central obesity (CO) is a risk factor for both preeclampsia and cardiovascular disease. Whether CO contributes to further worsening of arterial health after preeclampsia remains unclear. Our objective was to evaluate the effect of CO and previous preeclampsia on arterial hemodynamics. Methods and Results We studied 40 women with previous preeclampsia (<6 years) and 40 age-matched controls with previous normotensive pregnancy in the same timeframe. We estimated arterial hemodynamics with validated techniques combining applanation tonometry and echocardiography. CO was defined as a waist-to-hip ratio ≥0.85. Differences in arterial hemodynamics across the 3 groups (preeclampsia with CO, preeclampsia without CO, and controls) were assessed with multivariable linear regression models adjusted for potential confounders. Twenty-six (65%) of the participants with preeclampsia had CO compared with 18 (45%) controls. Mean waist-to-hip ratio in patients with preeclampsia with CO, those with preeclampsia and no CO, and controls was 0.94±0.05, 0.80±0.04, and 0.83±0.07, respectively. In multivariable analyses, women with preeclampsia and CO had higher central blood pressure, arterial stiffness (carotid-femoral pulse wave velocity), steady arterial load (systemic vascular resistance), and wave reflections (reflected pressure wave amplitude, augmentation index) compared with controls ( <0.05 for each). Fewer hemodynamic domains were altered in the preeclampsia with no CO group, with higher central diastolic blood pressure, systemic vascular resistance, and wave reflections than controls ( <0.05). Conclusions Women with previous preeclampsia who also experience CO have the greatest alterations in arterial health and hemodynamics. Patients with preeclampsia with CO may represent a higher-risk subgroup who could be targeted for risk stratification and primary prevention of cardiovascular disease.